Hypoxia Selection of Death-resistant Cells - Zheng Dong; Jinzhao Wang (2004)
Under hypoxia, some cells are irreversibly injured and die, whereas others can adapt to the stress and survive. The molecular and genetic basis underlying cellular sensitivity to hypoxic injury is unclear. Here we have selected death-resistant cells by repeated episodes of hypoxia. The selected cells are cross-resistant to apoptosis induced by staurosporine, azide, and cisplatin. These cells up-regulate Bcl-X(L), an anti-apoptotic protein. Bcl-X(L) interacts with the pro-apoptotic molecule Bax and abrogates its toxicity in mitochondria, resulting in the preservation of mitochondrial integrity, cytochrome c, and cell viability. Down-regulation of Bcl-X(L) by antisense oligonucleotides or the newly identified Bcl-X(L) inhibitor chelerythrine restores cellular sensitivity to injury and death. Thus, Bcl-X(L) is a key molecule for hypoxia selection of death resistance. These findings may have important implications for the development of solid tumors where hypoxia selects for death-resistant cells that are inert to cancer therapy.